2019
DOI: 10.2196/14006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Three Antecedents of Patient Compliance for Users of Peer-to-Peer Online Health Communities: Cross-Sectional Study

Abstract: BackgroundOver the past 50 years, patient noncompliance has appeared as a major public health concern and focus of a great deal of research because it endangers patient recovery and imposes a considerable financial burden on health care systems. Meanwhile, online health communities (OHCs) are becoming more common and are commonly used by individuals with health problems, and they may have a role in facilitating compliance. Despite this growing popularity, little is known about patient compliance predictors for… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 53 publications
0
27
0
1
Order By: Relevance
“…Engagement with OHCs promoted superusers’ sense of personal control/agency/self-efficacy over their illness, particularly when adopting the informal role of wise mentors or supporters to other users. Interestingly, a recent study indicated that patients gained empowerment through OHCs, which was positively related to patient commitment to the physician and to patient compliance with the proposed treatment [ 2 ]. Moreover, there is evidence that users who are high engagers (such as superusers who are themselves patients) exhibit the greatest improvement in patient activation measure (PAM; a measure that captures the extent to which people feel engaged and confident in taking care of their condition) in HealthUnlocked OHCs, even if the average change in PAM across all levels of engagement is not clinically meaningful [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Engagement with OHCs promoted superusers’ sense of personal control/agency/self-efficacy over their illness, particularly when adopting the informal role of wise mentors or supporters to other users. Interestingly, a recent study indicated that patients gained empowerment through OHCs, which was positively related to patient commitment to the physician and to patient compliance with the proposed treatment [ 2 ]. Moreover, there is evidence that users who are high engagers (such as superusers who are themselves patients) exhibit the greatest improvement in patient activation measure (PAM; a measure that captures the extent to which people feel engaged and confident in taking care of their condition) in HealthUnlocked OHCs, even if the average change in PAM across all levels of engagement is not clinically meaningful [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent work has suggested that taking part in online communities for people with long-term conditions (LTCs) improves illness self-management [ 1 ] and adherence to treatment [ 2 ], produces positive health-related outcomes [ 3 - 5 ], facilitates shared decision making with health care professionals (HCPs) [ 6 - 8 ], and may even reduce mortality [ 9 ]. There is also evidence that self-management support interventions can reduce health service utilization [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This also begets consideration of developing alternatives and complements to social media as sources of reliable health information hosting and exchange, with several recently launched in response to COVID-19 misinformation. Online health communities (OHCs) have drawn increasing interest in the domain of virtual social networks due to their potential to amplify positive impact such as peer-support and quality data as a source of health evidence (Smith et al, 2017;Audrain-Pontevia et al, 2019), as well as mitigate against negative impact through policies against the promotion of inaccurate information, as well as configurations that involve medical practitioners in moderation and content generation (Eysenbach, 2000;AskDr, 2020).…”
Section: What Lies Aheadmentioning
confidence: 99%
“…les personnes ayant survécu au cancer (Jansen et collab., 2015) et les personnes asthmatiques (Farzandipour et collab., 2017); Amélioration de l'autogestion : Les applications mobiles en santé permettent d'améliorer la gestion du diabète pour les personnes diabétiques (Bonoto et collab., 2017); Acquisition de connaissances : Les interventions en ligne permettent aux patients d'acquérir des connaissances sur leurs conditions de santé (Solomon, Wagner et Goes, 2012); Amélioration de la communication : L'utilisation d'une application mobile en santé permet d'améliorer la communication avec les professionnels de la santé (Lu et collab., 2018); Amélioration potentielle au traitement prescrit par le médecin : La santé mobile semble apporter des bénéfices pour améliorer l'adhérence à la médication (Hamine et collab., 2015). La participation du patient dans les communautés en ligne de patients accroît son adhésion au traitement prescrit par le médecin (Audrain-Pontevia, Menvielle et Ertz, 2019). (Gartner, 2018); Meilleur usage des soins en maisons de retraite : L'utilisation de la télémédecine permet d'améliorer les soins en maisons de retraite (Breen et Zhang, 2008).…”
Section: Chez Les Patients Chez Les Professionnels De La Santéunclassified